Analisis Literatur: Tantangan dan Peluang Public-Private Partnership (PPP) dalam Pembiayaan Pendidikan Dasar dan Menengah di Kalimantan Timur - Anita, Anita; Wulandari, Yuli; Puspitasari, Ni Luh Gede Dian; Mulawarman, Widyatmike Gede; Haryaka, Usfandi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to analyze the challenges and opportunities of implementing Public-Private Partnership (PPP) in financing primary and secondary education in East Kalimantan. Through a literature review of various national and international sources, the study identifies several key obstacles in PPP implementation, including unclear regulations, limited capacity of local government, and imbalances in the interests between the public and private sectors. The issue of sustainability in financing is also a significant challenge. However, there are considerable opportunities for the development of PPP, driven by the substantial need for educational infrastructure, advances in educational technology, and the potential for adopting PPP practices from more developed countries. This study recommends several key actions, including the formulation of clearer and more detailed policies, strengthening institutional capacity, providing fiscal incentives to the private sector, and enhancing transparency and accountability mechanisms in PPP implementation. These measures aim to optimize the role of PPP in promoting equity and improving the quality of education in East Kalimantan.